Leptalpheus pereirai sp. nov., a new alpheid shrimp from Panama and Venezuela (Decapoda: Caridea) - Anker, Arthur; Caripe, Jonathan Vera (Zootaxa, 2016)
A new species of the infaunal alpheid shrimp genus Leptalpheus Williams, 1965 is described based on material from three localities on the Caribbean coast of Panama and Isla Chimana Grande, Venezuela. Leptalpheus pereirai sp. nov. belongs to a group of species characterised by the presence of well-developed adhesive disks on the major chela and appears to dwell in burrows of the large callianassid ghost shrimp, Glypturus acanthochirus Stimpson 1866.